The Interaction between Product Market and Financing Strategy: The Role of Venture Capital - Hellmann, Thomas; Puri, Manju (Review of Financial Studies, 2000)
Journal Article The Interaction between Product Market and Financing Strategy: The Role of Venture Capital Get access Thomas Hellmann, Thomas Hellmann Stanford University Search for other works by this author on: Oxford Academic Google Scholar Manju Puri Manju Puri Stanford University Address correspondence to Manju Puri, Graduate School of Business, Stanford University, Stanford, CA 94305-5015, or e-mail: mpuri@gsb.stanford.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 13, Issue 4, October 2000, Pages 959–984, https://doi.org/10.1093/rfs/13.4.959 Published: 15 June 2015